A carbon-based Fe / Co / P / N co-doped bifunctional catalyst, preparation method and application thereof

By developing carbon-based Fe/Co/P/N co-doped dual-function catalysts, the problem of slow reaction speed of ORR and OER in zinc-air batteries is solved, efficient electrochemical performance and feasible application potential are achieved, and the raw materials are used are cheap, and the preparation method is simple and easy to repeat.

CN115172781BActive Publication Date: 2025-04-11SHANDONG ENERGY GRP CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210932032.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-04
Publication Date
2025-04-11
Estimated Expiration
2042-08-04

AI Technical Summary

Technical Problem

The slow kinetics of oxygen reduction reaction (ORR) and oxygen precipitation reaction (OER) in existing zinc-air batteries seriously hinder the actual use and output power of the battery, and the scarcity and expensive price of precious metal-based catalysts limit their application.

Method used

A carbon-based Fe/Co/P/N co-doped bifunctional catalyst was developed, and a polypyrroleate cobalt bimetallic polymer was formed by the reaction of carboxylated carbon nanotubes and tricobalt tetraoxide, ammonium persulfate and sodium ferrocyanide, and calcined and pyrolyzed under a nitrogen atmosphere to obtain a carbon-based Fe/Co/P/N co-doped bifunctional catalyst. The catalyst adsorbs small spherical polypyrroles and introduces phosphorus atoms through the carbon tube template, increasing the specific surface area and number of active sites of the catalyst.

Benefits of technology

The catalyst exhibits efficient ORR and OER electrochemical properties under alkaline conditions, with the half-wave potential of the oxygen reaction of 0.85V, which is better than commercial platinum/carbon; the overpotential of the oxygen precipitation reaction is 1.53V, which is better than commercial RuO2; the maximum output power in zinc-air batteries is 109mW/cm2, which is better than commercial platinum/carbon, and has feasible application potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115172781B_ABST
    Figure CN115172781B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a carbon-based Fe / Co / P / N co-doped bifunctional catalyst. The present invention uses carbon tubes as linear templates to successfully adsorb small spherical polypyrrole. The coating of polypyrrole avoids the sintering of iron-cobalt metal compounds during pyrolysis, and increases the number of iron-cobalt bimetallic active sites in the catalyst. After the introduction of phosphorus atoms into the catalyst for pyrolysis, the specific surface area of ​​the catalyst is greatly increased, which is beneficial to the exposure of active sites, promotes its adsorption of oxygen during the reaction, and limits the agglomeration of metal particles, thereby improving its bifunctional catalytic properties. The bifunctional catalyst of the present invention exhibits efficient oxygen reduction and oxygen evolution electrochemical performance under alkaline conditions. The present invention also provides a carbon-based Fe / Co / P / N co-doped bifunctional catalyst and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of energy materials, and in particular relates to a carbon-based Fe / Co / P / N co-doped bifunctional catalyst, a preparation method and application thereof. Background Art

[0002] Nowadays, the rapid growth of the global population, the continuous expansion of industrialization, the crazy rise in energy demand and the ongoing climate change have attracted widespread attention. The security and basic guarantee of future energy are issues we must face, so it is extremely important to find low-carbon, clean, low-cost and high-efficiency energy. People have begun to work on finding clean renewable energy, such as solar energy, wind energy, hydrogen energy, etc., but their supply has problems such as instability, intermittency and regionality.

[0003] In the exploration, people have found that fuel cells and metal-air batteries show great potential in high-capacity energy conversion systems. Fuel cells are clean energy devices that generate electricity as long as the fuel is continuously supplied. They are not limited by the Carnot cycle and have the advantages of high efficiency and no pollution. They have great application prospects in the future.

[0004] Zinc-air batteries are highly efficient and environmentally friendly batteries that use oxygen in the air as the positive electrode active material. Their raw materials are easily available, their specific energy is large, and they are environmentally friendly and resource-saving. They are also an environmentally friendly new energy source in the 21st century. They play an important role in the future energy structure transformation. Among them, oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) are important cathode reactions in rechargeable zinc-air batteries. However, the slow kinetics of oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) seriously hinder the practical use and output power of the battery. So far, the benchmark catalysts for these reactions are Pt-based and Ir / Ru-based catalysts, but the scarcity and high price of these precious metal-based catalysts in the earth's crust limit their application. Therefore, reducing the content of precious metals in the carrier without compromising the catalytic activity is the main goal of the rapidly developing catalytic field. Therefore, the development of bifunctional non-precious metal catalysts that can simultaneously achieve ORR and OER reactions is an important step in the application of clean and sustainable energy systems. Summary of the invention

[0005] The purpose of the present invention is to provide a carbon-based Fe / Co / P / N co-doped bifunctional catalyst, a preparation method and application thereof. The carbon-based Fe / Co / P / N co-doped bifunctional catalyst of the present invention can simultaneously improve the activity of ORR and OER and has high stability.

[0006] The present invention provides a method for preparing a carbon-based Fe / Co / P / N co-doped bifunctional catalyst, comprising the following steps:

[0007] A) mixing carboxylated carbon nanotubes and cobalt oxide with a mixed solvent, stirring and precooling at 0-4° C., then adding ammonium persulfate and sodium ferrocyanide decahydrate, stirring and dissolving, and then adding pyrrole to react to obtain a polypyrrole iron-cobalt bimetallic polymer;

[0008] The mixed solvent includes water, anhydrous ethanol and a surfactant;

[0009] B) grinding and mixing the polypyrrole iron cobalt bimetallic polymer and sodium hypophosphite to obtain a phosphorus-doped polypyrrole iron cobalt bimetallic polymer;

[0010] C) calcining and pyrolyzing the phosphorus-doped polypyrrole iron-cobalt bimetallic polymer under a nitrogen atmosphere to obtain a carbon-based Fe / Co / P / N co-doped bifunctional catalyst.

[0011] Preferably, the mass ratio of the carboxylated carbon nanotubes to cobalt oxide is (1.5-2.5):1.

[0012] Preferably, the volume ratio of the surfactant, the water, the anhydrous ethanol and the surfactant is (550-650):(130-160):1.

[0013] Preferably, the carboxylated carbon nanotubes and cobalt oxide are mixed with a mixed solvent under ultrasonic conditions and uniformly dispersed.

[0014] Preferably, the molar ratio of the ammonium persulfate to the sodium ferrocyanide decahydrate is 3:(3-5).

[0015] Preferably, the molar ratio of the ammonium persulfate to pyrrole is (1.5-2.5):1; the molar ratio of the sodium ferrocyanide decahydrate to pyrrole is (1-2):1.

[0016] Preferably, the mass of the sodium hypophosphite is 20-30% of the mass of the polypyrrole iron cobalt bimetallic polymer.

[0017] Preferably, the calcination temperature is 800-1000° C.; the calcination holding time is 1.5-2 hours; and the calcination heating rate is 3-8° C. / min.

[0018] The present invention provides a carbon-based Fe / Co / P / N co-doped bifunctional catalyst prepared by the preparation method described above.

[0019] The present invention provides the use of the carbon-based Fe / Co / P / N co-doped bifunctional catalyst as described above as an air cathode electrocatalyst in a rechargeable zinc-air fuel cell, a magnesium-air fuel cell or an aluminum-air fuel cell and a hydrogen-oxygen fuel cell.

[0020] The present invention provides a method for preparing a carbon-based Fe / Co / P / N co-doped bifunctional catalyst, comprising the following steps: A) mixing carboxylated carbon nanotubes and cobalt oxide with a mixed solvent, stirring and precooling at 0-4°C, then adding ammonium persulfate and sodium ferrocyanide decahydrate, stirring and dissolving, adding pyrrole, reacting, and obtaining a polypyrrole iron-cobalt bimetallic polymer; the mixed solvent comprises water, anhydrous ethanol, and a surfactant; B) grinding and mixing the polypyrrole iron-cobalt bimetallic polymer with sodium hypophosphite to obtain a phosphorus-doped polypyrrole iron-cobalt bimetallic polymer; C) calcining and pyrolyzing the phosphorus-doped polypyrrole iron-cobalt bimetallic polymer under a nitrogen atmosphere to obtain a carbon-based Fe / Co / P / N co-doped bifunctional catalyst. The present invention uses carbon tubes as linear templates to successfully adsorb small spherical polypyrrole, and the coating of polypyrrole avoids the sintering of iron-cobalt metal compounds during pyrolysis, and increases the number of iron-cobalt bimetallic active sites in the catalyst. After the introduction of phosphorus atoms into the catalyst for thermal decomposition, the specific surface area of ​​the catalyst is greatly increased, which is beneficial to the exposure of active sites, promotes its adsorption of oxygen during the reaction, and limits the agglomeration of metal particles, thereby improving its bifunctional catalytic properties. (2) The bifunctional catalyst of the present invention exhibits efficient oxygen reduction (ORR) and oxygen evolution (OER) electrochemical performance under alkaline conditions. The half-wave potential of the catalyst's oxygen reduction (ORR) electrochemical reaction is (0.85V vs. RHE), which is better than commercial platinum / carbon (0.84V); its overpotential of the oxygen evolution (OER) electrochemical reaction is (1.53V vs. RHE), which is better than commercial RuO2 (1.60V); (3) The maximum output power of the zinc-air battery assembled with this catalyst is 109mW / cm 2 , better than commercial platinum / carbon (78mW / cm 2 ), and has feasible application potential. (4) The raw materials used to obtain this catalyst are cheap and easy to obtain, the preparation method is simple and easy to repeat, and it has better stability than commercial platinum / carbon electrodes. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0022] Figure 1 This is a scanning electron microscope photograph of the Fe / Co / P / N co-doped carbon-based bifunctional catalyst obtained in Example 1 of the present invention;

[0023] Figure 2 XRD patterns of Fe / Co / P / N and Fe / Co / N co-doped carbon-based bifunctional catalysts obtained for Examples 1 to 4 of the present invention;

[0024] Figure 3 Cyclic voltammetry curves of Fe / Co / P / N and Fe / Co / N co-doped carbon-based bifunctional catalysts under alkaline conditions were obtained for Examples 1 to 4 of the present invention;

[0025] Figure 4 Oxygen reduction (ORR) linear scan curves of Fe / Co / P / N and Fe / Co / N co-doped carbon-based bifunctional catalysts and commercial Pt / C under alkaline conditions were obtained for Examples 1 to 4 of the present invention;

[0026] Figure 5 The linear scanning curves of the Fe / Co / P / N co-doped carbon-based bifunctional catalyst at different rotation speeds under alkaline conditions were obtained for Example 1 of the present invention;

[0027] Figure 6 Oxygen evolution (OER) linear scan curves of Fe / Co / P / N and Fe / Co / N co-doped carbon-based bifunctional catalysts under alkaline conditions were obtained for Examples 1 to 4 of the present invention;

[0028] Figure 7 The open circuit voltage curve of the rechargeable and dischargeable zinc-air fuel cell assembled in Example 1 of the present invention;

[0029] Figure 8 The power density and polarization curve of the rechargeable and dischargeable zinc-air fuel cell assembled in Example 1 of the present invention. DETAILED DESCRIPTION

[0030] The present invention provides a method for preparing a carbon-based Fe / Co / P / N co-doped bifunctional catalyst, comprising the following steps:

[0031] A) mixing carboxylated carbon nanotubes and cobalt oxide with a mixed solvent, stirring and precooling at 0-4° C., then adding ammonium persulfate and sodium ferrocyanide decahydrate, stirring and dissolving, and then adding pyrrole to react to obtain a polypyrrole iron-cobalt bimetallic polymer;

[0032] The mixed solvent includes water, anhydrous ethanol and a surfactant;

[0033] B) grinding and mixing the polypyrrole iron cobalt bimetallic polymer and sodium hypophosphite to obtain a phosphorus-doped polypyrrole iron cobalt bimetallic polymer;

[0034] C) calcining and pyrolyzing the phosphorus-doped polypyrrole iron-cobalt bimetallic polymer under a nitrogen atmosphere to obtain a carbon-based Fe / Co / P / N co-doped bifunctional catalyst.

[0035] The invention adds carboxylated carbon nanotubes and cobalt tetroxide into a reaction device, then adds a mixed solvent, ultrasonically disperses them uniformly, then adds a magneton, transfers them to a refrigerator and precools them under stirring conditions.

[0036] In the present invention, the mass ratio of the carboxylated carbon nanotubes to cobalt oxide is preferably (1.5-2.5):1, more preferably 2:1; the mixed solvent preferably includes water, anhydrous ethanol and a surfactant, the water is preferably deionized water, and the surfactant is preferably Tween 80; the volume ratio of water, anhydrous ethanol and surfactant is preferably (550-650):(130-160):1, more preferably 600:150:1. In the present invention, the ultrasonic time is preferably 20-40 minutes, more preferably 30 minutes.

[0037] In the present invention, the precooling temperature is preferably 0-4°C, more preferably 1-3°C, such as 0°C, 1°C, 2°C, 3°C, 4°C, preferably a range value with any of the above values ​​as the upper or lower limit; the precooling time is preferably 5-15min, more preferably 10min.

[0038] After precooling, the temperature of the precooling system is 0-4°C, and ammonium persulfate and sodium ferrocyanide decahydrate are added thereto, stirred for 3-5 minutes to dissolve the solid, and then pyrrole is added to react. This step of the reaction in the present invention realizes the coating and doping of iron-cobalt bimetallic by polypyrrole, and adopts a one-pot reaction, in which the carbon tubes and cobalt oxide added first respectively play the role of linear template and introduction of cobalt source, and they will be evenly dispersed by ultrasound under the action of surfactant, and the role of ammonium persulfate added secondly is to initiate the polymerization of pyrrole, and sodium ferrocyanide decahydrate introduces the required iron ions, and finally pyrrole is added to start the polymerization reaction. In addition, the pyrrole monomer used in the present invention will produce cationic radicals on the pyrrole chain during the polymerization process, which can successfully convert Fe(CN)6 4- A highly dispersed precursor of the iron active species is obtained by pre-anchoring it into the polypyrrole matrix through electrostatic interaction, which can effectively inhibit the agglomeration of metal particles caused by thermal decomposition.

[0039] In the present invention, the molar ratio of ammonium persulfate to sodium ferrocyanide decahydrate is preferably 3:(3-5), more preferably 3:4; the molar ratio of ammonium persulfate to pyrrole is preferably (1.5-2.5):1, more preferably (1.5-2):1; the molar ratio of sodium ferrocyanide decahydrate to pyrrole is (1-2):1, more preferably (1.5-2):1.

[0040] In the present invention, the reaction temperature is preferably 0-4°C, more preferably 1-3°C, such as 0°C, 1°C, 2°C, 3°C, 4°C, preferably a range value with any of the above values ​​as the upper or lower limit; the reaction time is preferably 5-8 hours, more preferably 6-7 hours.

[0041] After the reaction is completed, the solid-liquid mixture is filtered, the filter cake is washed with a large amount of deionized water, and placed in an oven for drying to obtain a polypyrrole iron-cobalt bimetallic polymer.

[0042] The invention mixes and grinds the prepared polypyrrole iron cobalt bimetallic polymer and sodium hypophosphite in an agate mortar to obtain a phosphorus-doped polypyrrole iron cobalt bimetallic polymer. The purpose of this step is to use a simple mixing and grinding method to achieve phosphorus doping and prepare for phosphating.

[0043] In the present invention, the mass of the sodium hypophosphite is 20-30% of the mass of the polypyrrole iron cobalt bimetallic polymer, such as 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, preferably a range value with any of the above values ​​as the upper or lower limit.

[0044] The phosphorus-doped polypyrrole iron-cobalt bimetallic polymer is calcined and pyrolyzed under a nitrogen atmosphere to obtain a carbon-based Fe / Co / P / N co-doped bifunctional catalyst.

[0045] In the present invention, the temperature of the calcination and pyrolysis is preferably 800-1000°C, more preferably 850-950°C, such as 800°C, 850°C, 900°C, 950°C, 1000°C, preferably a range value with the above arbitrary numerical values ​​as the upper or lower limit; the holding time of the calcination and pyrolysis is preferably 1.5-2 hours; the heating rate of the calcination and pyrolysis is preferably 3-8°C / min, such as 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, preferably a range value with the above arbitrary numerical values ​​as the upper or lower limit.

[0046] After calcination and pyrolysis, the temperature was lowered to 25°C at a rate of 3 to 8°C / min to obtain a carbon-based Fe / Co / P / N co-doped bifunctional catalyst.

[0047] The present invention also provides a carbon-based Fe / Co / P / N co-doped bifunctional catalyst, which is prepared according to the preparation method described above.

[0048] The present invention also provides an application of the carbon-based Fe / Co / P / N co-doped bifunctional catalyst as described above as an air cathode electrocatalyst in a rechargeable zinc-air fuel cell, a magnesium-air fuel cell or an aluminum-air fuel cell and a hydrogen-oxygen fuel cell.

[0049] The present invention provides a method for preparing a carbon-based Fe / Co / P / N co-doped bifunctional catalyst, comprising the following steps: A) mixing carboxylated carbon nanotubes and cobalt oxide with a mixed solvent, stirring and precooling at 0-4°C, then adding ammonium persulfate and sodium ferrocyanide decahydrate, stirring and dissolving, adding pyrrole, reacting, and obtaining a polypyrrole iron-cobalt bimetallic polymer; the mixed solvent comprises water, anhydrous ethanol, and a surfactant; B) grinding and mixing the polypyrrole iron-cobalt bimetallic polymer with sodium hypophosphite to obtain a phosphorus-doped polypyrrole iron-cobalt bimetallic polymer; C) calcining and pyrolyzing the phosphorus-doped polypyrrole iron-cobalt bimetallic polymer under a nitrogen atmosphere to obtain a carbon-based Fe / Co / P / N co-doped bifunctional catalyst. The present invention uses carbon tubes as linear templates to successfully adsorb small spherical polypyrrole, and the coating of polypyrrole avoids the sintering of iron-cobalt metal compounds during pyrolysis, and increases the number of iron-cobalt bimetallic active sites in the catalyst. After the introduction of phosphorus atoms into the catalyst for thermal decomposition, the specific surface area of ​​the catalyst is greatly increased, which is beneficial to the exposure of active sites, promotes its adsorption of oxygen during the reaction, and limits the agglomeration of metal particles, thereby improving its bifunctional catalytic properties. (2) The bifunctional catalyst of the present invention exhibits efficient oxygen reduction (ORR) and oxygen evolution (OER) electrochemical performance under alkaline conditions. The half-wave potential of the catalyst's oxygen reduction (ORR) electrochemical reaction is (0.85V vs. RHE), which is better than commercial platinum / carbon (0.84V); its overpotential of the oxygen evolution (OER) electrochemical reaction is (1.53V vs. RHE), which is better than commercial RuO2 (1.60V); (3) The maximum output power of the zinc-air battery assembled with this catalyst is 109mW / cm 2 , better than commercial platinum / carbon (78mW / cm 2 ), and has feasible application potential. (4) The raw materials used to obtain this catalyst are cheap and easy to obtain, the preparation method is simple and easy to repeat, and it has better stability than commercial platinum / carbon electrodes.

[0050] In order to further illustrate the present invention, a carbon-based Fe / Co / P / N co-doped bifunctional catalyst, its preparation method and application provided by the present invention are described in detail below in combination with embodiments, but it should not be construed as limiting the scope of protection of the present invention.

[0051] Embodiment 1:

[0052] Preparation of Polypyrrole Iron-Cobalt Bimetallic Polymer

[0053] Take 20mg of carboxylated carbon nanotubes and 10mg (0.04mmol) of cobalt tetraoxide in a clean three-necked flask. Add 60mL of deionized water, 15mL of anhydrous ethanol and 100μL (0.25mmol) of Tween 80 to the flask, disperse evenly by ultrasonication for 30min, add a magnetic bar and transfer to a refrigerator to stir and pre-cool for 10min at 0℃, then add 1.92g (8.4mmol) of ammonium persulfate and 5.42g (11.20mmol) of sodium ferrocyanide decahydrate to the flask, stir for 5min to dissolve the solid, and inject 400μL (5.6mmol) of pyrrole into the bottle. Stir and react for 6 hours at 0℃ in the refrigerator. After the reaction is completed, the solid-liquid mixture is filtered, the filter cake is rinsed with a large amount of deionized water, and dried to obtain a polypyrrole iron-cobalt bimetallic polymer.

[0054] Preparation of Phosphorus-doped Polypyrrole Iron-Cobalt Bimetallic Polymer

[0055] 200 mg of polypyrrole iron cobalt bimetallic polymer and 50 mg (0.565 mmol) of sodium hypophosphite were taken in an agate mortar, mixed and ground thoroughly to obtain phosphorus-doped polypyrrole iron cobalt bimetallic polymer.

[0056] Preparation of carbon-based bifunctional catalysts

[0057] 100 mg of phosphorus-doped polypyrrole iron-cobalt bimetallic polymer was placed in a clean porcelain boat and put into a high-temperature tube furnace under the protection of nitrogen. The temperature was first raised to 900°C at a rate of 5°C / min and maintained for 2 hours, and then cooled to 25°C at a rate of 5°C / min to obtain the Fe / Co / P / N co-doped carbon-based bifunctional catalyst Co2P@4Fe(PO3)2-NCNT-900. Figure 1 To obtain the scanning electron microscope photos of the corresponding catalyst samples.

[0058] Embodiment 2:

[0059] Preparation of Polypyrrole Iron-Cobalt Bimetallic Polymer

[0060] The polypyrrole iron-cobalt bimetallic polymer was obtained according to step S1 in Example 1.

[0061] Preparation of Phosphorus-doped Polypyrrole Iron-Cobalt Bimetallic Polymer

[0062] The iron-cobalt bimetallic polymer doped with polypyrrole was obtained according to step S2 in Example 1.

[0063] Preparation of carbon-based bifunctional catalysts

[0064] 100 mg of phosphorus-doped polypyrrole iron-cobalt bimetallic polymer was placed in a clean porcelain boat and put into a high-temperature tube furnace under the protection of nitrogen. The temperature was first raised to 800°C at a rate of 5°C / min and maintained for 2 hours, and then cooled to 25°C at a rate of 5°C / min to obtain the Fe / Co / P / N co-doped carbon-based bifunctional catalyst Co2P@4Fe(PO3)2-NCNT-800.

[0065] Example 3

[0066] Preparation of Polypyrrole Iron-Cobalt Bimetallic Polymer

[0067] Take 15mg of carboxylated carbon nanotubes and 7.5mg (0.03mmol) of cobalt tetraoxide in a clean three-necked flask. Add 60mL of deionized water, 15mL of anhydrous ethanol and 100μL (0.25mmol) of Tween 80 to the flask, disperse evenly by ultrasonication for 30min, add a magnetic particle and transfer to a refrigerator to stir and pre-cool for 10min at 0℃, then add 1.92g (8.4mmol) of ammonium persulfate and 5.42g (11.20mmol) of sodium ferrocyanide decahydrate to the flask, stir for 5min to dissolve the solid, and inject 400μL (5.6mmol) of pyrrole into the bottle. Stir and react for 6 hours at 0℃ in the refrigerator. After the reaction is completed, the solid-liquid mixture is filtered, the filter cake is rinsed with a large amount of deionized water, and dried to obtain a polypyrrole iron-cobalt bimetallic polymer.

[0068] Preparation of Phosphorus-doped Polypyrrole Iron-Cobalt Bimetallic Polymer

[0069] 200 mg of polypyrrole iron cobalt bimetallic polymer and 50 mg (0.565 mmol) of sodium hypophosphite were taken in an agate mortar, mixed and ground thoroughly to obtain phosphorus-doped polypyrrole iron cobalt bimetallic polymer.

[0070] Preparation of carbon-based bifunctional catalysts

[0071] 100 mg of phosphorus-doped polypyrrole iron-cobalt bimetallic polymer was placed in a clean porcelain boat and put into a high-temperature tube furnace under the protection of nitrogen. The temperature was first raised to 900°C at a rate of 5°C / min and maintained for 2 hours, and then cooled to 25°C at a rate of 5°C / min to obtain the Fe / Co / P / N co-doped carbon-based bifunctional catalyst Co2P@3Fe(PO3)2-NCNT-900.

[0072] Embodiment 4:

[0073] Preparation of Polypyrrole Iron-Cobalt Bimetallic Polymer

[0074] The polypyrrole iron-cobalt bimetallic polymer was obtained according to step S1 in Example 1.

[0075] Preparation of carbon-based bifunctional catalysts

[0076] 100 mg of doped polypyrrole iron-cobalt bimetallic polymer was placed in a clean porcelain boat and put into a high-temperature tube furnace under the protection of nitrogen. The temperature was first raised to 900°C at a rate of 5°C / min and maintained for 2 hours, and then cooled to 25°C at a rate of 5°C / min to obtain Fe / Co / N co-doped carbon-based bifunctional catalyst CoFe2O4-NCNT-900.

[0077] X-ray diffraction test

[0078] The catalyst samples obtained in Examples 1 to 4 were subjected to powder X-ray diffraction at a test angle of 20 to 80 degrees. Figure 2 To obtain the X-ray diffraction patterns of the corresponding catalyst samples, it was found that Examples 1 to 3 all formed two different metal phosphides Fe(PO3)2 and Co2P, while Example 4 formed a bimetallic compound CoFe2O4.

[0079] Fabrication of oxygen reduction working electrode

[0080] Weigh 5 mg of the catalyst sample obtained in Example 1-4 and pour it into a mortar to grind it. After grinding, place the catalyst in a 2 mL black-covered glass vial, add 800 μL of a 3% Nafion ethanol mixed solution by volume to the bottle, shake it slightly to mix, and then ultrasonicate for 30 minutes to evenly disperse the catalyst. Polish the electrode with an aluminum oxide polishing powder with a size of 50 nm, rinse it with ultrapure water, and then wipe it with lens paper. Use a pipette to transfer 5 μL of the prepared solution and drop it on a polished rotating disk electrode (diameter 5 mm). After the droplets are evenly spread and dried naturally, repeat this operation once more. After completion, test the electrochemical catalytic performance of the sample. Figure 3 Shown are the cyclic voltammetry curves of the catalyst samples obtained in Examples 1-4. In a 0.1M KOH electrolyte solution under O2 saturation conditions, an obvious oxygen reduction reaction (ORR) characteristic peak appears in the voltage range of 0.2-1.0V, indicating that these materials have effective electrocatalytic activity for the ORR reaction, and the reduction peak voltage is between 0.84-0.85V; while in a 0.1M KOH electrolyte solution under N2 saturation conditions, a featureless smooth curve without a reduction peak is shown in the same range. Figure 4 What is shown is the oxygen reduction (ORR) linear scanning curve of the catalyst samples obtained in Examples 1-4 in an electrolyte solution (0.1M KOH) under O2 saturation conditions at a rotation speed of 1600 rpm, and the half-wave potential is 0.84-0.85 V. By comparison, it is found that the half-wave potential (0.84 V) is comparable to that of commercial platinum / carbon, and is more positively shifted. Among them, Co2P@4Fe(PO3)2-NCNT-900 is positively shifted by 10 mv, indicating that the catalyst has a more efficient ORR catalytic activity. Figure 5 What is shown is the linear scanning curve of the catalyst sample obtained in Example 1 in an electrolyte solution saturated with O2 (0.1M KOH) at different rotation speeds. Calculation by the KL equation shows that the reaction occurring under the catalysis of the material is an ORR reaction with a four-electron dominant path, indicating that the dissolved O2 has good first-order reaction kinetics and shows ORR catalytic activity. Figure 6 What is shown is the linear scan curve of oxygen evolution (OER) of the catalyst samples obtained in Examples 1 to 4 in an electrolyte solution (1M KOH) under O2 saturated conditions at a rotation speed of 1600 rpm. The oxygen evolution overpotential is 1.53-1.56 V, which shows an oxygen evolution overpotential that is more negatively shifted than commercial ruthenium dioxide (1.60 V). Among them, Co2P@4Fe(PO3)2-NCNT-900 is 70 mv more negatively shifted, indicating that the catalyst has better OER catalytic activity. Therefore, Co2P@4Fe(PO3)2-NCNT-900 has the most outstanding dual-functional properties.

[0081] Preparation of air electrode

[0082] A mixed solution was prepared by mixing 5% Nafion solution, ultrapure water and ethanol in a volume ratio of 3:30:70. The catalyst sample obtained in Example 1 was ultrasonically dispersed in the mixed solution, and then drop-coated on a carbon paper electrode and dried to obtain a catalyst loading of 1 mg / cm 2 The air electrode was made by the same steps using commercial platinum / carbon as a comparative catalyst. A zinc-air fuel cell was formed with the air electrode as the cathode, the zinc sheet as the anode, and the electrolyte as a mixed solution of 6M KOH solution and 0.2M zinc acetate. The open circuit voltage and polarization curve of the battery were obtained by testing at room temperature and pressure. Figure 7 The open circuit voltage of the zinc-air fuel cell produced in Example 7 is shown in the figure as 1.51 V, which is greater than that of a single cell using commercial platinum / carbon as an ORR catalyst under the same conditions (1.47 V), and has a certain continuous output stability. Figure 8 This is the polarization curve of the zinc-air fuel cell produced in Example 7. The corresponding limiting power density is calculated to be 109 mW / cm 2 , which is also greater than that of a single cell (78 mW / cm 2 ), so it is believed that this material has feasible application potential.

[0083] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a carbon-based Fe / Co / P / N co-doped bifunctional catalyst, comprising the following steps: A) mixing carboxylated carbon nanotubes and cobalt oxide with a mixed solvent, stirring and precooling at 0-4° C., then adding ammonium persulfate and sodium ferrocyanide decahydrate, stirring and dissolving, and then adding pyrrole to react to obtain a polypyrrole iron-cobalt bimetallic polymer; The mixed solvent includes water, anhydrous ethanol and a surfactant; B) grinding and mixing the polypyrrole iron cobalt bimetallic polymer and sodium hypophosphite to obtain a phosphorus-doped polypyrrole iron cobalt bimetallic polymer; C) calcining and pyrolyzing the phosphorus-doped polypyrrole iron-cobalt bimetallic polymer under a nitrogen atmosphere to obtain a carbon-based Fe / Co / P / N co-doped bifunctional catalyst.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the carboxylated carbon nanotubes to cobalt oxide is (1.5-2.5):

1.

3. The preparation method according to claim 1, characterized in that: The volume ratio of water, anhydrous ethanol and surfactant is (550-650):(130-160):

1.

4. The preparation method according to claim 1, characterized in that: The carboxylated carbon nanotubes and cobalt tetroxide are mixed with a mixed solvent under ultrasonic conditions and uniformly dispersed.

5. The preparation method according to claim 1, characterized in that: The molar ratio of the ammonium persulfate to the sodium ferrocyanide decahydrate is 3:(3-5).

6. The preparation method according to claim 1, characterized in that: The molar ratio of the ammonium persulfate to pyrrole is (1.5-2.5):1; the molar ratio of the sodium ferrocyanide decahydrate to pyrrole is (1-2):

1.

7. The preparation method according to claim 1, characterized in that: The mass of the sodium hypophosphite is 20-30% of the mass of the polypyrrole iron cobalt bimetallic polymer.

8. The preparation method according to claim 1, characterized in that: The calcination temperature is 800-1000° C.; the calcination heat preservation time is 1.5-2 hours; and the calcination heating rate is 3-8° C. / min.

9. A carbon-based Fe / Co / P / N co-doped bifunctional catalyst prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the carbon-based Fe / Co / P / N co-doped bifunctional catalyst as claimed in claim 9 as an air cathode electrocatalyst in a rechargeable zinc-air fuel cell, a magnesium-air fuel cell or an aluminum-air fuel cell and a hydrogen-oxygen fuel cell.

Citation Information

Patent Citations

  • Hollow chain-shaped nitrogen-doped carbon nanotube package iron carbide dual-functional oxidization-reduction catalyst synthesized by one-step calcination method

    CN106972180A

  • Preparation method and application of carbon-based non-noble metal oxygen reduction catalyst

    CN110707337A